Regulatory elements common to the Bacillus pumilus and Bacillus subtilis trp operons. - Kuroda, M I (1986)
The trp operon regulatory region of Bacillus pumilus was cloned and sequenced. The cloned B. pumilus trp promoter-leader region functioned in Bacillus subtilis to express the adjacent leukocyte interferon A gene on a multicopy transcriptional fusion plasmid, pBpIFI. In strains carrying this plasmid, anthranilate synthetase levels were elevated, possible due to titration of a B. subtilis trp regulatory factor by multiple copies of the transcript of the plasmid-borne B. pumilus trp leader region. The B. pumilus trp promoter was recognized efficiently in vitro by B. subtilis sigma 43 RNA polymerase. Approximately 12% of the transcripts produced in vitro terminated in the leader region immediately following synthesis of a transcript structure resembling rho-independent terminators of enteric bacteria. An analogous terminator exists in the B. subtilis trp leader transcript. Nucleotide sequence comparison of the B. pumilus and B. subtilis trp leader regions revealed conservation of these and other sequences that could form transcript secondary structures postulated to regulate transcription termination in B. subtilis (H. Shimotsu, M.I. Kuroda, C. Yanofsky, and D.J. Henner, J. Bacteriol. 166:461-471, 1986). We propose that two elements implicated in B. subtilis trp operon regulation are conserved in the related organism B. pumilus: alternative transcription antiterminator and terminator structures in the leader transcript, and a trans-acting factor present in limiting amounts that is required for transcription termination in the leader region.